The development and application of a specialised word list: the case of Fabrication - Coxhead, Averil [Verfasser]; Mclaughlin, Emma [Verfasser]; Reid, Aleeshea [Verfasser] (My University, 2019)
"Learners in the trades are faced with learning a large amount of technical vocabulary along with the content of their field, but they do not tend to encounter this language outside their courses of study. This technical vocabulary is a core element in their developing knowledge of their trade and their learner identity. This article focuses first on identifying technical vocabulary in Fabrication using specialised written and spoken corpora, and through extensive checking with experts in the field as well as reference sources. A technical word list of 1079 types was developed, along with a list of common abbreviations and their meanings and a list of proper nouns. The technical word list covers over 30% of the vocabulary in the written Fabrication corpus and just over 9% of the spoken Fabrication corpus. The second part of the article discusses this vocabulary in light of the concept of vocational thresholds and provides suggestions for incorporating the word list into pedagogy, including an apprenticeship approach in which a focus on literacy/literacy acquisition is embedded into content teaching. Suggestions for future research are also included." (Author's abstract ; BIBB-Doku)
Keywords: G 1.2.4.1.4 Verarbeitendes Gewerbe; L 1 Curricula & Lehrpläne; Fachsprache; Lerninhalt; Fertigung; Lesekompetenz; Lehrer